Association of living alone and living alone time with hypertension among Chinese men aged 80 years and older: a cohort study - Xiang Wang; Xiang Wang; Miao Dai; Jingsong Xu (Frontiers Media S.A., 2024)
ObjectiveThere is little evidence of the influence of living alone on hypertension risk among men 80 years or older. Additionally, the influence of living alone duration on hypertension risk lacks thorough investigation. Hence, this cohort study examines living alone and its duration's link to hypertension risk in this specific group.MethodsWe included 2009 older men aged ≥80 years without hypertension from the Chinese Longitudinal Healthy Longevity Survey in the 2008 wave. Follow-up was conducted in the 2011 wave. Multivariable Cox proportional hazards models estimated hazard ratios (HRs) and 95% confidence intervals (CIs) to assess hypertension risk related to living alone and living alone time.ResultsWe included 2,009 older men, with a mean age of 90.7 years (standard deviation: 6.8). Over a median follow-up of 2.9 (1.3-3.0) years, 573 participants (28.5%) developed hypertension. Living alone was significantly associated with a higher hypertension risk than living with family (HR: 1.42; 95% CI 1.11-1.80). When compared to living with family, the hypertension risk was increased in the first quartile of living alone time (0-6.1 years) (HR: 1.76; 95% CI 1.16-2.66), the second quartile (6.1-10.6 years) (HR: 1.56; 95% CI 1.07-2.29), and the third quartile (10.6-19.3 years) (HR: 1.66; 95% CI 1.08-2.55). Surprisingly, no significant association was found in the fourth quartile (≥19.3 years) with hypertension risk. Stratified and Interaction analyses indicated no significant interaction effects between subgroups. Sensitivity analyses yielded consistent results.ConclusionLiving alone was independently associated with an increased risk of hypertension in older men. The highest risk was found in those with the least time alone. These findings imply that social isolation and lack of companionship could be pivotal in hypertension development. Furthermore, the study highlights the need to consider living alone duration when assessing its impact on health outcomes.